If l_i \: , \: m_i \: , \: n_i \: ; \: i \: = \: 1,2,3 denote the directions of cosines of three mutually perpendicular vectors i

Question

If l_i \: , \: m_i \: , \: n_i \: ; \: i \: = \: 1,2,3 denote the directions of cosines of three mutually perpendicular vectors in the space , prove that \sf{AA^T \: = \: I},

Where, {\sf{A \: = \:  \left[   \begin{array}{c c c}l_1&m_1&n_1 \\  l_2&m_2&n_2  \\ l_3&m_3&n_3\end{array}\right]} }

in progress 0
Maria 3 weeks 2021-08-23T06:46:09+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-23T06:47:36+00:00

    Given :

    \mathsf{l_{i},\:m_{i},\:n_{i}\:(i=1,2,3)} (i=1,2,3) denote the direction cosines of three mutually perpendicular vectors in space.

    Then,

    \mathsf{{l_{1}}^{2}+{m_{1}}^{2}+{n_{1}}^{2}=1}

    [tex]\mathsf{{l_{3}}^{2}+{m_{3}}^{2}+{n_{3}}^{2}=1}

    \mathsf{l_{1}l_{2}+m_{1}m_{2}+n_{1}n_{2}=0}

    \mathsf{l_{2}l_{3}+m_{2}m_{3}+n_{2}n_{3}=0}

    \mathsf{l_{3}l_{1}+m_{3}m_{1}+n_{3}n_{1}=0}

    \mathsf{A}=\left|\begin{array}{ccc}\mathsf{l_{1}}&\mathsf{m_{1}}&\mathsf{n_{1}}\\ \mathsf{l_{2}}&\mathsf{m_{2}}&\mathsf{n_{2}}\\ \mathsf{l_{3}}&\mathsf{m_{3}}&\mathsf{n_{3}}\end{array}\right|

    Then, \mathsf{A'}=\left|\begin{array}{ccc}\mathsf{l_{1}}&\mathsf{l_{2}}&\mathsf{l_{3}}\\ \mathsf{m_{1}}&\mathsf{m_{2}}&\mathsf{m_{3}}\\ \mathsf{n_{1}}&\mathsf{n_{2}}&\mathsf{n_{3}}\end{array}\right|

    \therefore \mathsf{AA'}=\left|\begin{array}{ccc}\mathsf{l_{1}}&\mathsf{m_{1}}&\mathsf{n_{1}}\\ \mathsf{l_{2}}&\mathsf{m_{2}}&\mathsf{n_{2}}\\ \mathsf{l_{3}}&\mathsf{m_{3}}&\mathsf{n_{3}}\end{array}\right| \left|\begin{array}{ccc}\mathsf{l_{1}}&\mathsf{l_{2}}&\mathsf{l_{3}}\\ \mathsf{m_{1}}&\mathsf{m_{2}}&\mathsf{m_{3}}\\ \mathsf{n_{1}}&\mathsf{n_{2}}&\mathsf{n_{3}}\end{array}\right|

    =\left|\begin{array}{ccc}\mathsf{{l_{1}}^{2}+{m_{1}}^{2}+{n_{1}}^{2}}&\mathsf{l_{1}l_{2}+m_{1}m_{2}+n_{1}n_{2}}&\mathsf{l_{3}l_{1}+m_{3}m_{1}+n_{3}n_{1}}\\ \mathsf{l_{1}l_{2}+m_{1}m_{2}+n_{1}n_{2}}&\mathsf{{l_{2}}^{2}+{m_{2}}^{2}+{n_{2}}^{2}}&\mathsf{l_{2}l_{3}+m_{2}m_{3}+n_{2}n_{3}}\\ \mathsf{l_{3}l_{1}+m_{3}m_{1}+n_{3}n_{1}}&\mathsf{l_{2}l_{3}+m_{2}m_{3}+n_{2}n_{3}}&\mathsf{{l_{3}}^{2}+{m_{3}}^{2}+{n_{3}}^{2}}\end{array}\right|

    =\left|\begin{array}{ccc}\mathsf{1}&\mathsf{0}&\mathsf{0}\\ \mathsf{0}&\mathsf{1}&\mathsf{0}\\ \mathsf{0}&\mathsf{0}&\mathsf{1}\end{array}\right|

    =\mathsf{I_{3}}

    \rightarrow \mathsf{AA'=I}

    Hence proved.

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )